An approach to estimate the barrier height for magnetisation reversal in Dy2 SMMs using ab initio calculations. Issue 42 (20th October 2020) - Dey, Sourav; Rajaraman, Gopalan
Abstract : A model equation to relate the computed barrier to experimental U eff for Dy2 has been proposed. This offers a way to estimate a reliable value U eff values using ab initio calculations using X-ray structure as the only input. Abstract : Although ab initio CASSCF calculations yield a good numerical estimate of barrier height for magnetisation reversal for mononuclear Dy(iii ) SIMs, obtaining a reliable value for higher nuclearity clusters such as Dy2 are challenging. By analysing ab initio computed data of thirty-one different Dy2 SMMs, we propose a model equation that relates the calculated barrier heights to the experimental values and offers a viable way to predict the barrier heights in Dy2 SMMs.